If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2(x + 1) + 8 = 20 Reorder the terms: 4x + -2(1 + x) + 8 = 20 4x + (1 * -2 + x * -2) + 8 = 20 4x + (-2 + -2x) + 8 = 20 Reorder the terms: -2 + 8 + 4x + -2x = 20 Combine like terms: -2 + 8 = 6 6 + 4x + -2x = 20 Combine like terms: 4x + -2x = 2x 6 + 2x = 20 Solving 6 + 2x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2x = 20 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 20 + -6 2x = 20 + -6 Combine like terms: 20 + -6 = 14 2x = 14 Divide each side by '2'. x = 7 Simplifying x = 7
| 21(x+1/7)=6 | | 2x^2+6x-6=0 | | 4x+8=4(x+2) | | 8x-2x=18 | | 2x^2+6x-6=p | | 5x+2.5y=15.00 | | 3t^2+2t+1=0 | | 3x-3=-2x+27 | | 5-2y=14x+3 | | 10x-7x=9 | | 5(x+1)=16 | | 2(5b-1)-3b=26 | | 9Y-7=5Y+7 | | -7x+5y=-6 | | 3x+5=-65-4x | | 24c^3+4c^2-20c=0 | | 8.5=8.50x | | 3(5a+4)-8=19 | | (x-6)+(2x-6)=39 | | 30x+4=x | | -4x+8=6 | | 106-6x=12x+22 | | 6x+16=2x+40 | | -3p+8=-7p+-12 | | 14x-9=39-16x | | 2(-x+6)-(-1-x)+3x-8=4(10x-5)-14x+6+8-2x+7x | | 9Y-7=11+7Y | | 8(3+b+1)=4(b+3)-9 | | 7d+4=8+-d | | (3ym^7)=(11y^6m^4) | | 5(x+2)-4=16 | | -5g+9=-6 |